1991
DOI: 10.1063/1.105608
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular magnetization in Ni/Pt multilayers

Abstract: Articles you may be interested inGrowth modes of nanocrystalline Ni/Pt multilayers with deposition temperature J. Appl. Phys. 102, 043525 (2007); 10.1063/1.2769785 X-ray magnetic circular dichroic magnetometry on Ni/Pt multilayers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…This is in agreement with our result on Ni/Ag [10] and on Ni/Pd by den Broeder et al [11]. However, we have shown that in the Ni/Pt system a strong perpendicular anisotropy is present arising from the surface anisotropy [12]. It is well known that the surface anisotropy arises from the local crystal fields and hence should not only depend on the state of the interface but also on the electronic structure of the neighboring metal.…”
Section: Resultssupporting
confidence: 92%
“…This is in agreement with our result on Ni/Ag [10] and on Ni/Pd by den Broeder et al [11]. However, we have shown that in the Ni/Pt system a strong perpendicular anisotropy is present arising from the surface anisotropy [12]. It is well known that the surface anisotropy arises from the local crystal fields and hence should not only depend on the state of the interface but also on the electronic structure of the neighboring metal.…”
Section: Resultssupporting
confidence: 92%
“…Krishnan et al 1 found in Ni͞Pt multilayers a perpendicular magnetization for Ni-layers with a thickness <1 nm. The same authors showed that one can get higher anisotropy values at the same thickness by evaporating at higher temperatures (200 ± instead of 30 ± ), which leads to positive values of the effective anisotropy for Ni-layer thicknesses <1.9 nm.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the work in the past was done using Co-based systems, but recently similar results were reported for Ni-based multilayers. [1][2][3] Unlike the Co-based systems where the Co layers can have the face-centered cubic (fcc) or the hexagonal compact packing (hcp) structure, 4 the Ni-, Pt-, and Pd-layers in the Ni͞Pt and Ni͞Pd systems always have the fcc structure at all temperatures, and therefore influences from phase transformations on the anisotropy can be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt/Ni multilayers were prepared by sequential deposition under ultrahigh vacuum using a dual e-beam system [7]. The samples were deposited onto glass substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Structure, magnetic and magnetooptic properties of Ni containing multilayers including selected results on polar Kerr spectroscopy were the subject of [4]-[6]. The perpendicular magnetic anisotropy has been demonstrated in both Pt/Ni and Pd/Ni systems [4,7]. The polar Kerr effect in Pt/Ni multilayers was the subject of [8].…”
Section: Manuscript Received February Is 1993mentioning
confidence: 99%